Lawyers and the Making of Constitutions: Making Constitutions in the South Pacific: Architects and Excavators - Frame, Alex (Victoria University of Wellington Law Review, 2002)
The author discusses the nature of constitutions from the view of two perspectives: that of the "architects", who take a downward-facing approach to constitution drafting by using robust rights that stand the test of time; and the "excavators", who take a bottom-up approach by taking existing rights enshrined in law and society and codifying them into a written constitution. The architects’ perspective is useful as it provides a good framework in which customary usage can develop, whereas the excavators’ historical approach is similar to the application of common law precedents in the courts. The author argues that, given time and stability, both perspectives should ideally lead to the same place. The paper concludes with the author’s legal advice to the Cook Islands regarding the formation of a constitution of their own.